Perancangan Alat Angkat Jaring Ikan Kapasitas 300 Kg - Aswandi, Baso; Sisworo, Raden Rinova; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2022)
Fishing net lifting equipment is a tool used to lift fish catches from the sea surface to the ship. This study aims to design a fishing net lifter according to the size of the tool and has the strength of the material that is safe to use, in this study the main system is the YL802-4 type driving motor, hooks with SC42 kg/mm2 material, steel ropes with type 6x19 +1 fiber core, pulley, drum roller rope with cast iron material with material strength 1000kg/cm2, transmission type i= 40 and INP profile steel frame with profile size bar height profile= 80mm, profile width= 42 mm with a cross-sectional area of 758 mm2 , in order to lift a load of 300 kg. For the main size of this tool has a stem height of 1500mm, length of arm span 1000mm, elbow support 1250 mm.Keywords: lifting equipment, design, motor drive